Prevalence and Dimensions of Burnout Syndrome among Ecuadorian University Faculty: An Initial Diagnostic Analysis for the Development of Preventive Models - Margoth, Solórzano Vera María; Rosiand, Manrique Alva; Manuel, Macías Ramírez; Enrique, Ortiz Porras Jorge; Dean, Duran Janampa Darwin (Journal of Ecohumanism, 2026)
This study examines the prevalence and patterns of burnout syndrome among university faculty in Ecuador through an initial diagnostic assessment aimed at informing future preventive interventions. The Maslach Burnout Inventory (MBI) was administered to 103 faculty members from a public higher education institution representing various academic programs. The results indicate concerning levels in two of the three assessed dimensions. High depersonalization was identified in 54.37% of participants, while 98.06% reported low levels of personal accomplishment, reflecting a substantial risk of professional disengagement. In contrast, emotional exhaustion showed a more heterogeneous distribution, with low, moderate, and high levels observed across the sample. These findings reveal the presence of significant psychosocial risks within the academic work environment and underscore the need to strengthen institutional strategies that promote faculty well-being. Furthermore, the study highlights the importance of developing organizational management models focused on preventing burnout and supporting sustainable academic performance. Overall, this research provides contextualized empirical evidence that enhances understanding of burnout in Ecuadorian higher education and supports the formulation of preventive policies within university systems.